1998
DOI: 10.1149/1.1838390
|View full text |Cite
|
Sign up to set email alerts
|

Effect of  O 2 Addition on the Deposition of Pt Thin Films by Metallorganic Chemical Vapor Deposition

Abstract: Platinum thin films were deposited on Si02/Si substrates at a deposition temperature of 325°C by metallorganic chemical vapor deposition using Pt-hexafluoroacetylacetonate as a precursor. It was found that the addition of the proper amount of 02 gas was essential to deposit high-quality Pt thin films. Dense Pt thin films with smooth surfaces and high electrical conductivity were deposited above a critical 02 flow rate of 50 sccm. The introduction of 02 gas made the Pt films partially oxidized, resulting in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…In comparison, a prior ALD Pt deposition study using MeCpPtMe 3 /Air ALD process at the same temperature (300 • C) yielded near-bulk resistivity of Pt only after 50 nm-thick Pt film was deposited. 16 Further, compared with the resistivity of chemical vapor deposited Pt (13-25 μ · cm), 17 the resistivity of the continuous ALD Pt film, in this study, is found to be ∼11 μ · cm, which is practically the bulk Pt resistivity (10.6 μ · cm).…”
Section: Resultsmentioning
confidence: 50%
“…In comparison, a prior ALD Pt deposition study using MeCpPtMe 3 /Air ALD process at the same temperature (300 • C) yielded near-bulk resistivity of Pt only after 50 nm-thick Pt film was deposited. 16 Further, compared with the resistivity of chemical vapor deposited Pt (13-25 μ · cm), 17 the resistivity of the continuous ALD Pt film, in this study, is found to be ∼11 μ · cm, which is practically the bulk Pt resistivity (10.6 μ · cm).…”
Section: Resultsmentioning
confidence: 50%
“…The curve is asymmetric because the volume of the film being illuminated is larger at small incoming angles. The preferred (111) orientation is typical for the face-centered cubic (fcc) metals and has been reported also for CVD-grown platinum films. , Since the growth rate (40 nm h -1 ) of the ALD platinum films is relatively low, the platinum atoms have enough time to migrate on the surface and to arrange in the (111) orientation with the lowest surface energy.
4 (a) XRD pattern of a 110-nm-thick platinum film and (b) rocking curve of the (111) reflection (2θ = 39.9°).
…”
Section: Resultsmentioning
confidence: 83%
“…There is confirmation that oxygen-rich atmospheres will produce oxides even in CVD [102] and that the resistivity of the films are a strong function of the degree of oxidized material [103].…”
Section: Related Techniquesmentioning
confidence: 96%